An ambient temperature, CO2-assisted solution processing of amorphous cobalt sulfide in a thiol/amine based quasi-ionic liquid for oxygen evolution catalysis. Issue 68 (8th August 2017) - Zhao, Xinhui; Jiang, Jingyun; Xue, Zhimin; Yan, Chuanyu; Mu, Tiancheng
Abstract : Amorphous cobalt sulfide nanosheets were synthesized from a 1, 2-ethanedithiol/ n -butylamine quasi-ionic liquid with the assistance of compressed CO2 at ambient temperature. Abstract : We report the synthesis of CoS x nanosheets from a 1, 2-ethanedithiol/ n -butylamine quasi-ionic liquid with the assistance of compressed CO2 at ambient temperature. The CoS x achieves a current density of 10 mA cm −2 at an overpotential of 271 mV for the oxygen evolution reaction. Furthermore, our method is applicable to the fabrication of other transition metal chalcogenides.